Time to Relapse After Short-Term or Long-Term Sertraline Treatment for Severe Premenstrual Syndromes - Freeman, Ellen W. (2009)
CONTEXT: The duration of treatment after achieving a satisfactory response is an unanswered question in the treatment of premenstrual syndrome (PMS). This information is needed given the improvement provided by medication versus the side effects and costs of drugs. OBJECTIVES: Compare rates of relapse and time to relapse between short-term and long-term sertraline treatment administered in the luteal phase. DESIGN: An 18-month survival study with a randomized, double-blind switch to placebo after 4 months or 12 months of sertraline treatment. SETTING: Academic medical center. PARTICIPANTS: 174 PMS/PMDD patients. MAIN OUTCOME MEASURE: Relapse, defined as symptoms returned to the entry criterion level assessed by daily ratings. RESULTS: The relapse rate was 41% during long-term treatment compared to 60% after short-term sertraline treatment, with a median time to relapse over 8 months versus 4 months (hazard ratio 0.58; CI 0.34, 0.98; P=0.04). Subjects with severe baseline symptoms were more likely to relapse compared to the low-moderate group (hazard ratio= 2.02, CI 1.18, 3.41; P=0.01) and were more likely to relapse with short-term treatment (P=0.03). Length of treatment did not affect relapse for subjects with low to moderate symptoms (P=0.50). Subjects who reached remission were least likely to relapse (hazard ratio= 0.22; CI 0.10, 0.45; P<0.001). Further analysis comparing relapse in the first 6 months on placebo in each treatment group had similar results. CONCLUSIONS: The relapse rate was significantly greater after short -term treatment compared to long-term treatment. The relapse rate was also high during extended drug treatment. Subjects with severe symptoms at baseline were most likely to relapse and relapsed more swiftly, regardless of treatment duration. The findings suggest that the severity of symptoms at baseline and symptom remission with treatment should be considered in determining the duration of treatment.